Single snapshot imaging method in multiple‐input multiple‐output radar with sparse antenna array. Issue 5 (1st June 2013) - Gu, Fufei; Chi, Long; Zhang, Qun; Zhu, Feng
Abstract : In this study, a single snapshot imaging method of the moving targets in multiple‐input multiple‐output (MIMO) radar with sparse antenna array is proposed. First, a configuration of sparse antenna array is presented and then, on the basis of this, an imaging method based on compressed sensing theory is put forward. With this method, the image of a moving target can be achieved via single snapshot imaging processing. It not only can avoid motion compensation processing as required by conventional inverse synthetic aperture radar imaging, but also can dramatically reduce the number of the antenna elements, which is a quite large number in the typical configuration of MIMO radar system with linear antenna array. Finally, the effectiveness of this method is validated by the simulation results.